Toward the Development of Dynamic Innovation Capabilities in a Hospitality Industry: A Case Study in Glamping Service Provider - Anjar Priyono; Siti Nurulhuda Binti Nordin; Syadiyah Abdul Shukor (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2025)
Non Index Publication (Tier 4)